Analisis Pemidanaan terhadap Anak Pelaku Tindak Pidana Pemaksaan Berbuat Cabul terhadap Anak Korban (Studi Putusan Nomor: 7/Pid.Sus-Anak/2024/PN.Gdt) - Decky, Radha Aulia Putri; Dewi, Erna; Muhtadi, Muhtadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The increasing number of children involved as perpetrators in sexual crimes against fellow minors raises serious concerns in criminal law and child protection. This research examines the criminal sentencing imposed on a child who committed forced indecent acts against a child victim, as reflected in Decision No. 7/Pid.Sus-Anak/2024/PN.Gdt. The study aims to analyze (1) how the sentencing is carried out and (2) whether the sentencing aligns with the purposes of punishment. This research applies a normative juridical and empirical juridical approach, with data collected through literature review and field interviews with judges, prosecutors, and legal scholars. The results show that the child offender was sentenced to 7 years in the Class II Child Development Institution (LPKA) in Bandar Lampung and 6 months of job training at LPKS Insan Berguna. The judge’s decision was based on legal (juridical), philosophical, and sociological considerations. It was also grounded in the integrative theory of punishment, which combines retributive and rehabilitative aims. The punishment not only served as a deterrent and accountability for the committed crime but also aimed to reform and reintegrate the child into society. The study concludes that the imposed sentence was proportionate, aligned with statutory requirements, and reflected the best interests of the child without neglecting public justice and protection.